2018
DOI: 10.1177/0743558417753953
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalized Adolescents’ Use of Mobile Technologies for Learning, Communication, and Well-Being

Abstract: Hospitalized adolescents experience significant needs beyond medical treatment. They require emotional support for anxiety and stress, educational support for learning, and social support to reduce isolation. This qualitative study explored the use of mobile technologies to connect students to their schools, classmates, and families in an effort to reduce their isolation and disrupted schooling experiences. We conducted in-depth interviews with 18 hospitalized adolescents aged 12 to 18, 29 teachers, and four p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…There have been a variety of studies that demonstrate positive outcomes for adolescents when using a technology-based peer support interventions. This body of research demonstrated that these interventions provide a space for information exchange, reduction of social isolation, improved perceptions of normalcy, and to make friends (Greco et al, 2001;Franklin et al, 2003;Liu et al, 2015;Kramer et al, 2018;Maor, 2020). Specifically in the context of self-disclosure, Lee et al (2013) found that social support played a full, mediating role between selfdisclosure and well-being on social networking sites.…”
Section: Social Supportmentioning
confidence: 99%
“…There have been a variety of studies that demonstrate positive outcomes for adolescents when using a technology-based peer support interventions. This body of research demonstrated that these interventions provide a space for information exchange, reduction of social isolation, improved perceptions of normalcy, and to make friends (Greco et al, 2001;Franklin et al, 2003;Liu et al, 2015;Kramer et al, 2018;Maor, 2020). Specifically in the context of self-disclosure, Lee et al (2013) found that social support played a full, mediating role between selfdisclosure and well-being on social networking sites.…”
Section: Social Supportmentioning
confidence: 99%
“…A literature review by Maor and Mitchem [7] confirmed that using technologies to withstand for the hospitalized youth’s academic path, as well as to impact on their well-being, are helpful (e.g., the “PEEBLES” program [60]). In this line of thought, the authors reinforce their claim that the use of technology in the hospital context could be an important tool to engage adolescents in learning [61]. Most of these studies used technology to maintain the connection between the hospitalized youngsters and their learning context [49,50,53,62], promoting their motivation to learn and facilitating their return to school.…”
Section: Introductionmentioning
confidence: 86%
“…It is precisely in this perspective, where mobile technologies play a fundamental role, although always taking into account the vulnerability of these devices due to cyber-attacks on privacy and data exploitation [41]. Providing students with educational opportunities [42] that do not require temporal and spatial limitations [43][44][45] will modify the traditional physical relationships between teachers, students and learning [46,47].…”
Section: Tools and Strategies In Plementioning
confidence: 99%